2011
DOI: 10.2174/156720511796717212
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up Study of Olfactory Deficits, Cognitive Functions, and Volume Loss of Medial Temporal Lobe Structures in Patients with Mild Cognitive Impairment

Abstract: Prediction of MCI to dementia conversion can be improved by supplementing the neuropsychological tests with odor identification tests. A follow up study of hippocampus volume reduction, OI performance and cognitive functions deterioration will further increase prediction accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 0 publications
2
30
1
Order By: Relevance
“…Lastly, altered response to an attractant scent in AD mice is consistent with reported deficits in odor-based memory formation [60]. This deficit may be conceptually related to the early olfactory deficits in MCI patients [61], who are at particular risk to develop AD [62, 63]. Taken together, the current behavioral model is consistent with previous observations and interpretations.…”
Section: Discussionsupporting
confidence: 88%
“…Lastly, altered response to an attractant scent in AD mice is consistent with reported deficits in odor-based memory formation [60]. This deficit may be conceptually related to the early olfactory deficits in MCI patients [61], who are at particular risk to develop AD [62, 63]. Taken together, the current behavioral model is consistent with previous observations and interpretations.…”
Section: Discussionsupporting
confidence: 88%
“…86, 87 Indeed, change in olfactory identification has been strongly associated with pathological changes in the medial temporal lobe structures. 88 These studies strongly imply a primary role for olfactory dysfunction as an indicator of pathological cognitive decline and dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Some neuroimaging studies have examined the clinical and neuroanatomical correlates of olfactory performance in individuals with MCI and AD. Reduced olfactory identification was associated with smaller hippocampal volume in amnestic MCI and AD (Murphy et al, ; Lojkowska et al, ; Kjelvik et al, ). The 18 F‐fluorodeoxyglucose (FDG) PET study showed a relationship between olfactory identification score and FDG uptake in early AD (Forster et al, ), and associations between the olfactory tract integrity and metabolic activity in medial temporal lobe and posterior cortical structures in MCI (Cross et al, ).…”
Section: Discussionmentioning
confidence: 99%